Ondel-ondel kekinian: boneka besar Betawi di zaman modern - Mita Purbasari; M Dwi Marianto; M Agus Burhan (Institut Seni Indonesia Yogyakarta, 2019)
Ondel-ondel is an ancient Betawi’s art work named Barongan, in simple shaped of one pair off greater puppets, complete with the music companion. At the beginning, ondel-ondel was a part of Betawinese scared rituals then become one of Jakarta’s icons. Ondel-ondel can be found until today either in performing arts and decoration element form. In its development as the decoration element form, ondel-ondel is not only the great puppet for buildings and stages decorator, but also has been positioned as a part of cultural tourism and society living needs. Moreover, ondel-ondel has been used to be an inspiration to produce souvenir to support industry. Ondel-ondel is not longer just made in big size, but also in mini size in form of 2 or 3 dimensions, so it is easy to be carried as a souvenir, which represents Jakarta and Betawi. To find out the value behind the sign changed, this qualitative research used the semiotic approach. Connection or relation between symbolic sign in ondel-ondel structure and building elements were collaborated with society condition as the background and impact of the society on that time to get the value. The changes of ondel-ondel’s meanings and functions in building elements have been produced and contracted as its user way of thinking based on its form and context. The meaning interpretation of ondel-ondel craftsman and audience in particular time would be different with government’s policies. Key words: ondel-ondel, building elements, souvenir, meaning, function